Wdowy w universum wczesnych chrześcijan – trzy perspektywy badawcze - Nakonieczny, Rafał (Vox Patrum, 2022)
This article presents the findings of a metascientific analysis of the topic of the widow's situation in the early Christian community. This topic is studied today from at least three perspectives. It is still interesting for historians studying the development of early Christian communities. Secondly, the situation of women (including widows) is a very interesting field of research for authors of the critical school (not always definitely feminist) wondering about the possibility of an alternative reconstruction of social relations. The assumption of these studies is often that the originally high position of women in the Christian community was gradually diminished. A special emphasis in this study however is placed on the third research aspect, which is the presentation of the widows' situation in the ancient world (biblical, Hellenistic, early Christian) as an impulse for a deep reflection on our attitude to the weakest individuals. These include – as in the past – lonely and elderly women (often widowed). Numerous contemporary studies postulate that efforts should be made to prevent their marginalization and loneliness. This is demanded by Christian anthropology and the properly understood virtue of solidarity - without excluding anyone. One possibility for the realization of such an objective may be the reactivation of the orders of widows in contemporary Christian communities.